Indonesia's Critical View on Public Sector Accounting: Insights from M Nastir's Thought - Zuhdi, Rahmat; Sudarma, Made (Accounting Department, 2023)
Purpose — This research attempts to introduce a typical Indonesian critical thought, M. Natsir's perspective, which can be used to study public sector accounting. Design/methodology/approach– This study used the narrative literature review method. This article then compiled an outline of M Natsir's critical methodology, which focuses on the emancipatory revolution based on the spirit of Islamic values and continues to prioritize democracy and national unity. It hopes the methodology can construct the [financial] state management to align with the nation's interests. Findings — The results of this study indicate that the development of paradigmatic studies in the field of accounting opens great opportunities to complete, perfect, and even present concepts in new accounting models that are in line with the needs of the ages, as shown in this article, which borrows the thoughts of M Natsir. This reflection serves as a methodological basis to present the concept of an emancipatory revolution based on the spirit of Islam and the love for motherland values growing within Indonesian society. Therefore, people's conceptions of love for material things can be oriented in a more beneficial direction for society. It can also construct a country's best financial management method. Practical implications — This research encourages the presence of public sector accounting studies without forgetting the context of local values, love of country, and Islamic spirit in the form of good state financial management. Originality/value—This research framework critiques the concept and practice of NPM and its accrual accounting as a derivative of neoliberal ideology. It also examines the roots of economic policies that are not oriented towards the interests of the people in general. Using this proposed framework, it is hoped that the spirit of love for the motherland and the spirit of Islam can be felt in the state's financial accounting and management. Paper type — Research Papers